Comparative Burden of Metabolic Dysfunction in Lean NAFLD vs Non-lean NAFLD - A Systematic Review and Meta-analysis - Tang, Ansel; Ng, Cheng Han; Phang, Poh Hui; Chan, Kai En; Chin, Yip Han; Fu, Clarissa Elysia; Zeng, Rebecca Wenling; Xiao, Jieling; Tan, Darren Jun Hao; Quek, Jingxuan; Lim, Wen Hui; Mak, Lung Yi; et al. (Clinical gastroenterology and hepatology, 2023)
Nonalcoholic fatty liver disease (NAFLD) is traditionally associated with obesity. However, there is a subtype of NAFLD, namely NAFLD in lean, that occurs without obesity. However, a recent call to redefine NAFLD to metabolic-associated fatty liver disease focuses on obesity and metabolic dysfunction. Criticism has arisen from the perceived over emphasis on systemic comorbidities, which may disadvantage the lean. The current analysis seeks to quantify the degree of metabolic dysfunction in NAFLD in lean and compare with NAFLD in overweight and obese and non-NAFLD. Medline and Embase databases were searched from inception to March 3, 2022. The inclusion criteria were articles with NAFLD in lean patients presenting with baseline metabolic parameters. Comparisons were conducted with subgroup analysis. Eighty-five articles were included in the meta-analysis. NAFLD in lean accounted for 13.11% (95% confidence interval [CI], 10.26%–16.62%) of the global population and 14.55% (95% CI, 11.32%–18.51%) in Asia. The degree of metabolic dysfunction was weight dependent with significantly less metabolic dysfunction in NAFLD in lean subjects as compared with NAFLD in overweight counterparts. For NAFLD in lean, only 19.56% (95% CI, 15.28%–24.69%) of the subjects were diabetic, whereas 45.70% (95% CI, 35.01%–56.80%) of obese subjects with NAFLD had diabetes (P < .01). Fasting blood glucose and systolic and diastolic blood pressure values were significantly lower in subjects with NAFLD in lean than in overweight and obese. The current analysis highlights the weight-dependent nature of metabolic dysfunction in NAFLD. Lean subjects with NAFLD were significantly less metabolically unhealthy than were obese and overweight persons with NAFLD. An overreliance on metabolic dysfunction in defining fatty liver will be a flaw in potentially excluding previously characterized NAFLD. [Display omitted]